2018
DOI: 10.31801/cfsuasmas.443579
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Lq-Likelihood Estimation for the parameters of Marshall-Olkin Extended Burr XII Distribution

Abstract: Marshall-Olkin extended Burr XII (MOEBXII) distribution is proposed by Al-Saiari et al. (2014) to obtain a more ‡exible family of distributions. Some estimation methods like maximum likelihood, Bayes and M estimations are used to estimate the parameters of the MOEBXII distribution in literature. In this paper, we propose to use Maximum Lq (MLq) estimation method to …nd alternative estimators for the parameters of the MOEBXII distribution. We give some simulation studies and a real data example to compare the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…By deriving the asymptotic distribution of this test statistic, the authors have demonstrated its robustness both analytically and numerically, and they investigated the properties of both its influence function and its breakdown point. Also Ozdemir et al (2019) use the MLq estimation method to estimate the parameters of Marshall-Olkin extended Burr XII distribution and show that MLq estimation method outperform the ML. Recently, Dogru et al (2018) propose parameter estimation of the multivariate t distribution using the MLq estimation, provide that unlike the ML estimation the degrees of freedom parameters can be estimated along with the other parameters, and still gain the robustness.…”
Section: Introductionmentioning
confidence: 99%
“…By deriving the asymptotic distribution of this test statistic, the authors have demonstrated its robustness both analytically and numerically, and they investigated the properties of both its influence function and its breakdown point. Also Ozdemir et al (2019) use the MLq estimation method to estimate the parameters of Marshall-Olkin extended Burr XII distribution and show that MLq estimation method outperform the ML. Recently, Dogru et al (2018) propose parameter estimation of the multivariate t distribution using the MLq estimation, provide that unlike the ML estimation the degrees of freedom parameters can be estimated along with the other parameters, and still gain the robustness.…”
Section: Introductionmentioning
confidence: 99%